(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Knowledge Attitudes and Skills of Farmers in Tobacco Cultivation After Following SL-GAP in Subak Gede Sukawati, Sukawati District, Gianyar Regency. SL-GAP is a program implemented to overcome problems in tobacco cultivation in Subak Gede Sukawati. The purpose of this study was to determine the knowledge, attitudes and skills of farmers in tobacco cultivation after attending SL-GAP. The selection of the location with the purposive method, the research was conducted for 4 months, the number of respondents was 50 people and used qualitative descriptive data analysis methods. Assessment of knowledge, attitudes and skills using scores. Based on the discussion, the results obtained are that knowledge is categorized as high with a percentage of farmers as much as 54%, attitudes are in the category agree with the percentage of farmers as much as 40%, and the skills of farmers in tobacco cultivation in the field are categorized as good with a percentage of farmers as much as 27%, farmers are considered skilled in tobacco cultivation. Knowledge on fertilization is increased again, farmers do not understand the impact of using excess fertilizer and pay attention to plants from pests. Some farmers’ attitudes need to be changed so they don’t follow the previous cultivation method too much. Skills need to be retrained so that farmers use fertilizers according to recommendations, carry out irrigation and carry out pest control properly.